Fit to Forgive: Effect of Mode of Exercise on Capacity to Override Grudges and Forgiveness - Struthers, C. Ward; van Monsjou, Elizabeth; Ayoub, Mariam; Guilfoyle, Joshua R. (Frontiers in Psychology, 2017)
Forgiveness is important for repairing relationships that have been damaged by transgressions. In this research we explored the notion that the mode of physical exercise that victims of transgressions engage in and their capacity to override grudges are important in the process of forgiveness. Two exploratory studies that varied in samples (community nonstudent adults, undergraduate students) and research methods (nonexperimental, experimental) were used to test these predictions. Findings showed that, compared to anaerobic or no exercise, aerobic and flexibility exercise facilitated self-control over grudges and forgiveness (Studies 1 and 2), and self-control over grudges explained the relation between exercise and forgiveness (Study 2). Possible mechanisms for future research are discussed.